2022
DOI: 10.4236/ijohns.2022.116031
|View full text |Cite
|
Sign up to set email alerts
|

Cervicofacial Cystic Lymphangiomas and Review of the Literature: About 2 Cases at Donka National Hospital

Abstract: In this retrospective study, conducted over 7 years (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) at the ENT and Head and Neck Surgery Department of the Donka National Hospital, we report 2 cases of cervicofacial cystic lymphangiomas. They were a 28-monthold girl and a 2-year-old boy. The symptomatology was noted after their birth. Dyspnea and dysphagia were found in the boy. They had a satisfactory general condition. ENT examination noted a cystic-like tumor syndrome. Imaging showed evidence of a cystic ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The series by Komolafe et al [2] in Nigeria shows a mean age of 29.15 ± 8.12 years. The series by Keita et al [9] found a mean age of 42.21 years, with extremes of 16 and 64 years, and the 35 -44 age group was the most represented at 33.1%. On the other hand, European series such as that of Uldry et al [10], in Switzerland, reported 71.1% in the [50 -69] age bracket, and that of Sathirapanya et al [11] in Thailand, noted a mean age of 46 years, with extremes of 38 and 49.7 years.…”
Section: Discussionmentioning
confidence: 97%
“…The series by Komolafe et al [2] in Nigeria shows a mean age of 29.15 ± 8.12 years. The series by Keita et al [9] found a mean age of 42.21 years, with extremes of 16 and 64 years, and the 35 -44 age group was the most represented at 33.1%. On the other hand, European series such as that of Uldry et al [10], in Switzerland, reported 71.1% in the [50 -69] age bracket, and that of Sathirapanya et al [11] in Thailand, noted a mean age of 46 years, with extremes of 38 and 49.7 years.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the cystic lymphangioma has intimate relationships with the cervical venous system, the thoracic duct or the large lymphatic vein, and there is no real cleavage plane; the surgical procedure must be, as much as possible, complete to avoid recurrences. However, the concept of complete excision should not expose the patient to postoperative functional and aesthetic risks for a condition that remains benign [10]. The treatment of cystic lymphangiomas with sclerosing products has been mentioned by certain authors in the literature as first-line treatment [12] [18].…”
Section: Discussionmentioning
confidence: 99%
“…CH are benign, non-cancerous tumors arising from the lymphatic system, which develop in the neck. They can also develop following trauma or infection [ 1 ]. They can manifest themselves in a variety of locations, including the spermatic cord level, the mediastinum, the breast, the cervical area, the abdomen, the inguinal region, and the spleen [ 2 ].…”
Section: Introductionmentioning
confidence: 99%